Studentâ€™s Selfâ€Efficacy and Perceptions of Online Learning on the Use Learning Management System - Udin, Tamsik; Maufur, Syibli; Riyanto, Onwardono Rit (Universitas Pendidikan Ganesha, 2022)
Empirical evidence explained the current changes in teaching and learning due to the coronavirus pandemic, especially in Indonesia. This study investigates factors of self-efficacy and the impacts on online learning in one university in Indonesia. In this research, the theory of social cognitive integration is used in the online learning process. This type of quantitative research with an online questionnaire tool was applied to collect data from 156 students. The data were analyzed using the Structure equation modeling (SEM) approach proposed using the Lisrel software. This study shows the significance of self-efficacy in finishing online learning and self-efficacy in interacting during online learning. The impacts are seen in terms of comfortability and self-awareness of students to attend online learning. On the other hand, the effect of social interaction in online learning is categorized as an insignificant factor statistically to influence the subject's intentions. The conditions of solving the obstacles and handling the features in the learning management system (LMS) are essential to achieving success in online learningFrom the research results, self-efficacy factors have a positive impact on the implementation of e-learning and instructor support helps overcome technical obstacles. Moreover, this study contributes to the implementation and guidance of students behaviours to increase success in online learning.